2011
DOI: 10.1111/j.1468-3083.2010.03775.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of minor acute cutaneous wounds: importance of wound healing in a moist environment

Abstract: Moist wound care has been established as standard therapy for chronic wounds with impaired healing. Healing in acute wounds, in particular in minor superficial acute wounds - which indeed are much more numerous than chronic wounds - is often taken for granted because it is assumed that in those wounds normal phases of wound healing should run per se without any problems. But minor wounds such as small cuts, scraps or abrasions also need proper care to prevent complications, in particular infections. Local woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(117 citation statements)
references
References 70 publications
0
115
0
2
Order By: Relevance
“…Firstly, the moist local environment provided by hydrogels was conducive to wound healing [44]. Kant et al reported the similar results, they found that blank Pluronic F-127 gel gave rise to faster wound healing rate than normal saline due to its ability to provide a moisture environment to the wound surface [45].…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, the moist local environment provided by hydrogels was conducive to wound healing [44]. Kant et al reported the similar results, they found that blank Pluronic F-127 gel gave rise to faster wound healing rate than normal saline due to its ability to provide a moisture environment to the wound surface [45].…”
Section: Discussionmentioning
confidence: 93%
“…This clot releases several chemotactic substances such as vascular endothe- lial growth factor (VEGF), epithelial growth factor (EGF), platelet derived growth factor (PDGF), transforming growth factor-β (TGF-β), and immunoregulatory cytokines, providing a provisional matrix that allows cell migration (10). Some investigators divide the inflammatory phase into two distinct stages: 1) early inflammation (24 to 48 h after wounding) characterized by the massive presence of neutrophils, and 2) later inflammation (48 to 72 h after wounding) characterized by the influx of monocytes and macrophages to the wound site in order to remove germs and debris (11). In the phase of granulation tissue formation, the secretion of VEGF (by keratinocytes, macrophages, fibroblasts, platelets, and endothelial cells) attracts endothelial cells that begin to form new capillary tubes (12).…”
mentioning
confidence: 99%
“…Hydrocolloid dressings have previously been used in wound healing studies to provide a moist wound healing environment (Kiecolt-Glaser et al, 1995, Korting, Schoellmann & White, 2011. This means that there is faster epithelialisation compared with uncovered wounds and the prevention of eschar formation allows for more accurate assessments of wound reepithelialisation.…”
Section: Methodsmentioning
confidence: 99%